Distinct Impact of Three Different Statins on Arteriovenous Fistula Outcomes: A Retrospective Analysis. Issue 6 (November 2016) - Martinez, Laisel; Duque, Juan C.; Escobar, Luis A.; Tabbara, Marwan; Asif, Arif; Fayad, Fadi; Vazquez-Padron, Roberto I.; Salman, Loay H.
Purpose: Whether statins improve arteriovenous fistula (AVF) outcomes is still a matter of debate. Taking into consideration the existing physicochemical differences between individual drugs, this study evaluates the impact of three different statins (atorvastatin, rosuvastatin and simvastatin) on one-stage and two-stage AVF outcomes. Methods: Using a retrospective cohort of 535 patients, we analyzed the effects of each statin on primary failure and primary patency using multivariate logistic regressions and Cox proportional hazard models. Results: Out of the three statins analyzed, only atorvastatin improved the overall primary failure of AVF (odds ratio [OR] = 0.18, p = 0.005). Comparisons between the two AVF types demonstrated that this effect was due to a prominent reduction in primary failure of one-stage (OR = 0.03; p = 0.005), but not two-stage fistulas (OR = 0.43; p = 0.25). In contrast, primary patency of two-stage (hazards ratio [HR] = 0.51; p = 0.024), but not one-stage fistulas (HR = 0.98; p = 0.95), was improved by all statins as a group, but not by individual drugs. Conclusions: Our results suggest that the potential benefit of statins on AVF outcomes is a drug-specific and not a class effect, and that such effect is also influenced by the type of fistula.